Allotype-specific processing of the CD16a N45-glycan from primary human natural killer cells and monocytes. (21st January 2020) - Patel, Kashyap R; Roberts, Jacob T; Barb, Adam W
Abstract: Fc γ receptor IIIa/CD16a is an activating cell surface receptor with a well-defined role in natural killer (NK) cell and monocyte effector function. The extracellular domain is decorated with five asparagine (N)-linked glycans; N-glycans at N162 and N45 directly contribute to high-affinity antibody binding and protein stability. N-glycan structures at N162 showed significant donor-dependent variation in a recent study of CD16a isolated from primary human NK cells, but structures at N45 were relatively homogeneous. In this study, we identified variations in N45 glycan structures associated with a polymorphism coding for histidine instead of leucine at position 48 of CD16a from two heterozygous donors. It is known that H48 homozygous individuals suffer from immunodeficiency and recurrent viral infections. A mass spectrometry analysis of protein isolated from the primary natural killer cells of individuals expressing both CD16a L48 and H48 variants demonstrated clear processing differences at N45. CD16a H48 displayed a greater proportion of complex-type N45 glycans compared to the more common L48 allotype with predominantly hybrid N45-glycoforms. Structures at the four other N-glycosylation sites showed minimal differences from data collected on donors expressing only the predominant L48 variant. CD16a H48 purified from a pool of monocytes similarly displayed increased processing at N45. Here, we provide evidence that CD16a processing is affected by the H48 residue in primary NK cells and monocytes from healthy human donors.